Infrared thermographic inspection of operating smokestacks - Vavilov V. P. Vladimir Platonovich (2002, 2002)
The general principles of the IR thermographic inspection of operating smokestacks are presented. The features of surface temperature distributions are illustrated for metallic, brick and concrete smokestacks. Typical IR thermograms are presented.